2020
DOI: 10.3389/fpls.2020.00223
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and Tolerance to Root Herbivory in Maize Were Mediated by Domestication, Spread, and Breeding

Abstract: Plants may defend against herbivory and disease through various means. Plant defensive strategies against herbivores include resistance and tolerance, which may have metabolic costs that affect plant growth and reproduction. Thus, expression of these strategies may be mediated by a variety of factors, such as resource availability, herbivory pressure, and plant genetic variation, among others. Additionally, artificial selection by farmers and systematic breeding by scientists may mediate the expression of resi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 94 publications
(158 reference statements)
3
24
1
Order By: Relevance
“…While previous studies showed that 10-OPEA increased in maize roots 7 days after WCR feeding, which was correlated with increases in LOX3 and other 9-LOXs [68], our data suggests that, relative to the maizes, BTEO can more readily activate this sub-branch of the 9-LOX pathway in response to WCR feeding. Coincident with this study's results, our previous study showed that BTEO was more resistant but less tolerant to WCR than MXLR and maizes generally [51]. Put together, this and our prior study's results suggest that the stronger resistance and weaker tolerance to WCR in BTEO compared to MXLR is likely due to elevated levels of induced jasmonates and low levels of IAA in BTEO, while defence in MXLR, and maize generally, is due to high constitutive levels of 9-oxylipins and IAA.…”
Section: With Domestication Maize Resistance To Root Herbivory Shiftsupporting
confidence: 86%
See 4 more Smart Citations
“…While previous studies showed that 10-OPEA increased in maize roots 7 days after WCR feeding, which was correlated with increases in LOX3 and other 9-LOXs [68], our data suggests that, relative to the maizes, BTEO can more readily activate this sub-branch of the 9-LOX pathway in response to WCR feeding. Coincident with this study's results, our previous study showed that BTEO was more resistant but less tolerant to WCR than MXLR and maizes generally [51]. Put together, this and our prior study's results suggest that the stronger resistance and weaker tolerance to WCR in BTEO compared to MXLR is likely due to elevated levels of induced jasmonates and low levels of IAA in BTEO, while defence in MXLR, and maize generally, is due to high constitutive levels of 9-oxylipins and IAA.…”
Section: With Domestication Maize Resistance To Root Herbivory Shiftsupporting
confidence: 86%
“…Prior studies showed that landrace maizes are planted on ~80% of the area devoted to maize in Mexico, encompassing mostly hillsides with poor soils, while improved commercial varieties are planted on the remaining ~20% of the area, and that farmers will plant commercial varieties on good soils and landraces on poorer soils, when they have a choice [73][74][75][76][77]. Finally, while US landraces (no longer planted commercially) and inbred lines were developed for the same environments, the availability of major soil nutrients, e.g., nitrogen, differed greatly between the early and late portions of the 20 th century, associated with intensification of maize production reliant on commercial (hybrid) varieties and other inputs (e.g., fertilizers and insecticides to support high crop productivity and offset insect injury) that began in the middle of that century [50,51,78,79]. For example, prior to the 1930s, few maize growers employed fertilizers because they were uneconomical or unavailable, while the use of synthetic nitrogen fertilizers nearly tripled between 1964 and 1985 [78][79][80].…”
Section: With Domestication Maize Resistance To Root Herbivory Shiftmentioning
confidence: 99%
See 3 more Smart Citations